EFFECTIVENESS TEST OF NIPAH EXTRACT AS LARVACIDE ON MOSQUITO LARVAE (Aedes aegpti) - Purba, Thadeus Mariode Triputra; Effendi, Irwan; Feliatra, Feli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2019)
This research was conducted in January - February 2019. The purpose of this study was to examine the effectiveness of mangrove extracts on stems and fruit on the growth of Aedes aegypti mosquito larvae and to know Lethal Concentration LC50 and Lethal Time LT50. The method used is the experimental method, with the experimental design is a completely randomized design (CRD). The treatment of nipah fruit and stem extract concentrations was 3%, 6% and 9% with contact time of 15 minutes, 30 minutes, 45 minutes 60 minutes, 120 minutes, 480 minutes and the number of replications 3 times with 2 trials. To find out (LC50) and (LT50), the data was analyzed using the SPSS program. The sample of this research is stem and nipah fruit taken in the mangrove area of Kayu Ara Village, Siak Regency. Aedes aegypti larvae are taken at a water reservoir next to the Arfaunas Mosque in Tampan District. The results showed that the stem and nipah fruit extracts had effective killing power against Aedes aegpti larvae. The extract that was more effective in killing mosquito larvae was the nipah fruit extract compared to the nipah stem extract seen in the number of larval deaths with LC50 = 3.398% and LT50 = 3.540 hours. This shows that the level of toxicity is quite toxic.